2017
DOI: 10.1111/1467-8578.12163
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among former students with special educational needs who are now in their mid‐30s

Abstract: This article discusses how psychosocial health in adolescence influences adult mental health among former students with special educational needs in Norway. These individuals have been followed prospectively from their teens and into their mid-30s. The study is inspired by life course perspectives with an emphasis on cumulative processes. The logistic regression analysis reveals that the risk of suffering from adult mental distress is higher among those with psychosocial difficulties in their juvenile years co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, examples of reasons stated by upper secondary school students themselves are commonly related to an unsupportive home and school environment and lack of the necessary adjustments to their educational needs [15][16][17]. Båtevik [13] concluded that, irrespective of gender, but particularly for women, graduation significantly increases the probability of employment for former students with SEN. Efforts to support students with SEN to obtain educational qualifications should be prioritised to decrease their risk of social and economic vulnerability, health problems [7,[18][19][20], loss of productive capacity, and costs for the welfare system. In a study by Yngve et al [21], students with SEN who received a student-centred information and communication technology (ICT) intervention in upper secondary school perceived a significantly more supportive school environment and a positive tendency in terms of increased school attendance.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
“…However, examples of reasons stated by upper secondary school students themselves are commonly related to an unsupportive home and school environment and lack of the necessary adjustments to their educational needs [15][16][17]. Båtevik [13] concluded that, irrespective of gender, but particularly for women, graduation significantly increases the probability of employment for former students with SEN. Efforts to support students with SEN to obtain educational qualifications should be prioritised to decrease their risk of social and economic vulnerability, health problems [7,[18][19][20], loss of productive capacity, and costs for the welfare system. In a study by Yngve et al [21], students with SEN who received a student-centred information and communication technology (ICT) intervention in upper secondary school perceived a significantly more supportive school environment and a positive tendency in terms of increased school attendance.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
“…Furthermore, experiencing SEN during upper secondary education increases the risk of mental health problems later in life. As an example, Myklebust and Myklebust (2017) found that upper secondary school students with SEN had an increased risk of mental distress in their thirties.…”
Section: Establishment In Work and Further Studies Among Students Witmentioning
confidence: 99%